Spatial and functional standards of social housing in Serbia: regulations, practice and users’ perception - Njegic, Tanja R (Arhitektura i urbanizam, 2020)
Adequate level of housing comfort, in terms of space, function and health, is one of the key factors of quality and sustainability of social housing. In post-socialist Serbia, the extremely residual system of provision in this sector has been a major challenge to achieve adequate quality standards for new social housing construction over the past two decades. Through a review of the national regulations in the field of planning, design and construction of social housing after 2000 and the results of the conducted empirical research on six completed projects (in Valjevo, Pančevo, Čačak, Kraljevo, Kragujevac and Belgrade), the paper discusses the situation, limitations and opportunities for improving current housing practices in this field. In the initial period of formation of the new housing system, through the recommendations for planning and design social housing was treated as below average standard and quality housing, but since 2009 its development through the legislative framework is increasingly directed towards the concept of sustainable housing development. At the same time, the results of the evaluation of the pioneering examples of practice in this area, realized in the period 2008-2010, indicate certain deficiency in terms of the application of sustainability criteria. Through a survey of tenants on satisfaction with various elements of housing comfort, the problems of overcrowding and inadequacy of housing conditions regarding functional and health aspects were observed in selected examples. It was found that the tenants are mostly satisfied with the level of thermal and light comfort in the apartments, while they expressed significant dissatisfaction due to the lack of auxiliary and open apartment areas, insufficient sound insulation and overall lower quality construction. In the concluding remarks, the results of the research are discussed and recommendations are given for the improvement of design standards and monitoring instruments in social housing programs in Serbia.